2015
DOI: 10.1007/s11999-015-4479-3
|View full text |Cite
|
Sign up to set email alerts
|

Women Demonstrate More Pain and Worse Function Before THA but Comparable Results 12 Months After Surgery

Abstract: Background Many studies report differences in patientreported outcome measures (PROMs) for men and women undergoing total hip arthroplasty (THA). Few studies have evaluated whether these are explained by corresponding differences in important preoperative factors. Questions/purposes (1) Are there differences between men and women in PROM scores preoperatively and 12 months after THA? (2) Do baseline differences in comorbidity, age, body mass index (BMI), and mental health status explain these differences in PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 43 publications
4
15
0
1
Order By: Relevance
“…Female sex was a risk factor for a lower MCS-12. This has been shown in other studies as well, including among women undergoing total hip arthroplasty [ 11 ]. This may also be impacted by fewer caregivers present for women than for men.…”
Section: Discussionsupporting
confidence: 80%
“…Female sex was a risk factor for a lower MCS-12. This has been shown in other studies as well, including among women undergoing total hip arthroplasty [ 11 ]. This may also be impacted by fewer caregivers present for women than for men.…”
Section: Discussionsupporting
confidence: 80%
“…Several studies have demonstrated that female patients have significantly worse preoperative functional outcome scores before total hip arthroplasty. 13,23 Mannion et al 20 evaluated pain and function 1 year after total hip arthroplasty and found that female patients had significantly lower baseline functional outcome scores. However, the authors noted no significant sex differences in outcome scores at 1-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Sex, age, and preoperative quality of life are factors that appear to have an effect on patient reported outcomes after surgery. 5 9 In addition, conditions such as pain, 5 function, 10 , 11 comorbidity, 12 , 13 BMI, 14 16 and underlying diseases prior to the operation 17 , 18 seem to play a role. Furthermore, expectations before surgery 4 , 19 , 20 and socioeconomic status 21 , 22 may influence patients’ reporting postoperatively.…”
Section: Introductionmentioning
confidence: 99%